2012
DOI: 10.1158/0008-5472.can-12-0487
|View full text |Cite
|
Sign up to set email alerts
|

Cell Death via DR5, but not DR4, Is Regulated by p53 in Myeloma Cells

Abstract: Myeloma cells are sensitive to TRAIL through the two death receptors DR4 and DR5. Because p53 directly modulates expression of death receptors, we investigated here whether p53 can modulate myeloma sensitivity to TRAIL. We found that p53 affects the sensitivity of myeloma cells to the DR5 agonistic human antibody lexatumumab but not the DR4 antibody mapatumumab. TP53 wild-type myeloma cells overexpressed DR5 in correlation with sensitivity to lexatumumab. Both nongenotoxic (nutlin-3a) and genotoxic (melphalan)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 48 publications
5
75
0
Order By: Relevance
“…TRAIL, which induces apoptosis via interactions with its death receptors DR4 and DR5, represents a promising candidate agent for the treatment of MM (11,42,43). Recent studies suggest that there is a correlation between TRAIL sensitivity and death receptor expression in cancer cells (44), thus the upregulation of death receptor expression renders MM cells more sensitive to the action of TRAIL.…”
Section: Discussionmentioning
confidence: 99%
“…TRAIL, which induces apoptosis via interactions with its death receptors DR4 and DR5, represents a promising candidate agent for the treatment of MM (11,42,43). Recent studies suggest that there is a correlation between TRAIL sensitivity and death receptor expression in cancer cells (44), thus the upregulation of death receptor expression renders MM cells more sensitive to the action of TRAIL.…”
Section: Discussionmentioning
confidence: 99%
“…8 Interestingly, taking all HCMLs together (median LD 50 =20.5 mM), we found that most HMCLs were efficiently killed by curcumin; we observed that 16 HMCLs were highly sensitive (LD 50 < 20.5 mM), and 6 HMCLs exhibited intermediate LD 50 values (20.5 mM LD 50 < 32.2 mM); only 7 HMCLs exhibited the highest LD 50 values (32,2 < LD 50 < 56 mM). Moreover, curcumin sensitivity was not dependent on TP53 status, since LD 50 were not statistically different between HMCLs exhibiting either wild type (median LD 50 18.4 mM) or abnormal TP53 (mutated, truncated or deleted) 12 (median LD 50 22.15 mM) (p=0.221) (Fig. 1C).…”
Section: Resultsmentioning
confidence: 90%
“…12,22 The HMCLs BCN; NAN1, ¡3, ¡7, ¡8 and ¡9; SBN; and XG1, ¡2, ¡5, ¡6, ¡7 and ¡11 were derived in Nantes or Montpellier laboratories in the presence of interleukin-6 (IL-6). KMS11, KMS12-PE and KMM1 HMCLs were kindly provided by Dr. Otsuki (Kurashiki, Japan), JJN3 was kindly provided by Dr. Van Riet (Brussels, Belgium), JIM3 was kindly provided by Dr. MacLennan (Birmingham, UK), Karpas 620 was kindly provided by Dr. Karpas (Cambridge, UK) and MM1S was kindly provided by Dr. Rosen (Chicago, IL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported that certain intracellular molecules can selectively affect the expression of different death receptors. For example, inhibition of p53 expression affects the expression of DR5 but not that of DR4 in myeloma cells (Surget et al, 2012). Thus, further clarification on the mechanism underlying IDO activity-regulated DR5 expression and further research is still needed.…”
Section: Discussionmentioning
confidence: 99%